Fast forwarding higher education institutions for global challenges - Amzat, Ismail Hussein; Yusuf, Byabazaire (Springer Singapore, 2016)
This book addresses various 21st century questions and challenges, especially the role of technology in upgrading teaching and learning in today’s society, and the role of higher education institutions in improving standards of living, economics, society and sustainability. It shares with readers the challenges of globalization to higher institutions concerning the issues relating to value creation management, branding and the impact on leadership in higher institutions.